2010
DOI: 10.1098/rsif.2010.0419
|View full text |Cite
|
Sign up to set email alerts
|

Rho-associated kinase-dependent contraction of stress fibres and the organization of focal adhesions

Abstract: Stress fibres and associated focal adhesions in cells constitute a contractile apparatus that regulates cell motility and contraction. Rho-kinase, an effector molecule of small GTPases, regulates non-muscle cell motility and contractility. Rho-kinase mediates the contraction of stress fibres in a Ca 2þ -independent manner, and is responsible for slower and more finely tuned contraction of stress fibres than that regulated by myosin light chain kinase activity in living cells. The specific inhibition of the Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 59 publications
(114 reference statements)
6
89
0
Order By: Relevance
“…MLCK could trigger MLC phosphorylation to enhance the actin-myosin interaction, which in turn increased the cell tension [50]. Without that, cells may maintain the cytoskeleton structure, but lose the cellular tension [51]. As the result, hMSCs with MLCK inhibited was unable to commit to myogenic differentiation in our study.…”
Section: Discussionmentioning
confidence: 64%
“…MLCK could trigger MLC phosphorylation to enhance the actin-myosin interaction, which in turn increased the cell tension [50]. Without that, cells may maintain the cytoskeleton structure, but lose the cellular tension [51]. As the result, hMSCs with MLCK inhibited was unable to commit to myogenic differentiation in our study.…”
Section: Discussionmentioning
confidence: 64%
“…The retraction dynamics yield quantitative information about the viscoelastic properties of the fiber, and the resulting change in cell shape lends insight into the contribution of the targeted SF to cell shape stability. We have previously used this approach to demonstrate that the mechanical properties of a SF depend strongly on whether the fiber is located at the cell center or periphery (Tanner et al, 2010), and that this is related to the differential control of these two SF populations by the myosin activators Rho-associated kinase (ROCK) and myosin light chain kinase (MLCK), respectively (Katoh et al, 2011;Katoh et al, 2007;Totsukawa et al, 2004). Moreover, disruption of peripheral SFs often triggers whole-cell adhesive disassembly and contraction, which has led us to speculate that central and peripheral SFs distribute their tensile loads differently across the cell-ECM interface and that this in turn gives rise to their differential contributions to cell shape stability.…”
Section: Introductionmentioning
confidence: 99%
“…During contraction of stress fibers, myosin mediates sliding of antiparallel actin filaments and plays a key role in stress fiber stability and cell motility (Hotulainen and Lappalainen, 2006). Notably, phosphorylation of MLC2 has been demonstrated to be a vital motor involved in motility (Chaturvedi et al, 2011;Katoh et al, 2011). Therefore, we investigated the expression and phosphorylation of MLC2 in our NDRG1 overexpression and knockdown models.…”
Section: Ndrg1 Inhibits F-actin Polymerization and Stressmentioning
confidence: 99%
“…It is reported that a key factor in stress fiber formation is the phosphorylation of myosin light chain 2 (MLC2) at Thr18/ Ser19 (Katoh et al, 2011). Cells have a complicated signaling network modulating MLC2 phosphorylation, among which the Rho-associated, coiled-coil-containing protein kinase 1 (ROCK1) pathway is one of the most crucial mechanisms in stimulating cross-linking of actin by myosin, leading to enhanced cancer cell contractility (Chaturvedi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%